Genome-wide characterization and expression analysis of the ADF gene family in response to salt and drought stress in alfalfa (Medicago sativa) - Shi, Mengmeng; Wang, Yike; Lv, Peng; Gong, Yujie; Sha, Qi; Zhao, Xinyan; Zhou, Wen; Meng, Lingtao; Han, Zegang; Zhang, Lingxiao; Sun, Yongwang (Frontiers in Plant Science, 2025)
The microfilament cytoskeleton, formed by the process of actin polymerization, serves not only to support the morphology of the cell, but also to regulate a number of cellular activities. Actin-depolymerizing factors (ADFs) represent a significant class of actin-binding proteins that regulate the dynamic alterations in the microfilament framework, thereby playing a pivotal role in plant growth and development. Additionally, they are instrumental in modulating stress responses in plants. The ADF gene family has been explored in various plants, but there was a paucity of knowledge regarding the ADF gene family in alfalfa (Medicago sativa), which is one of the most significant leguminous forage crops globally. In this study, a total of nine ADF genes (designated MsADF1 through MsADF9) were identified in the alfalfa genome and mapped to five different chromosomes. A phylogenetic analysis indicated that the MsADF genes could be classified into four distinct groups, with members within the same group exhibiting comparable gene structures and conserved motifs. The analysis of the Ka/Ks ratios indicated that the MsADF genes underwent purity-based selection during its evolutionary expansion. The promoter region of these genes was found to contain multiple cis-acting elements related to hormone responses, defence, and stress, indicating that they may respond to a variety of developmental and environmental stimuli. Gene expression profiles analyzed by RT-qPCR experiments demonstrated that MsADF genes exhibited distinct expression patterns among different organs. Furthermore, the majority of MsADF genes were induced by salt and drought stress by more than two-fold, with MsADF1, 2/3, 6, and 9 being highly induced, suggesting their critical role in resistance to abiotic stress. These results provide comprehensive information on the MsADF gene family in alfalfa and lay a solid foundation for elucidating their biological function.